Development of Submergence-Tolerant, Bacterial Blight-Resistant, and High-Yielding Near Isogenic Lines of Popular Variety, ‘Swarna’ Through Marker-Assisted Breeding Approach - Mohapatra, Shibani; Panda, Alok Kumar; Bastia, Akshaya Kumar; Mukherjee, Arup Kumar; Sanghamitra, Priyadarshini; Meher, Jitendriya; Mohanty, Shakti Prakash; Pradhan, Sharat Kumar (Frontiers in Plant Science, 2021)
The rice variety ‘Swarna’ is highly popular in the eastern region of India. The farmers of eastern India cultivate mainly rainfed rice and face the adverse effects of climate change very frequently. Rice production in this region is not stable. Swarna variety is highly susceptible to bacterial blight (BB) disease and flash flood which causes heavy reduction in the yield. Transfer of five target genes/QTLs was targeted into the variety, Swarna by adopting marker-assisted backcross breeding approach. Direct markers for Sub1A, OsSPL14, and SCM2 QTLs and closely linked markers for xa5 and Xa21 BB resistance genes were screened in the backcross progenies. Swarna-Sub1, CR Dhan 800, and Swarna-Habataki near-isogenic line were used as donor parents in the breeding program. True multiple F1 plant was identified for backcrossing and 796 BC1F1 seeds were generated. Foreground selection detected all the five target genes in six progenies in BC1F1 generation. The progeny containing all the target genes and more similar with the recipient parent was backcrossed and a total of 446 BC2F1 seeds were produced. Foreground screening detected 4 BC2F1 plants carrying the 5 target genes. A total of 2145 BC2F2 seeds were obtained from the best BC2F1 progeny. Screening of the progenies resulted in one plant with all 5 desirable genes, 3 plants with 4, and another 3 progenies carrying 3 genes in homozygous conditions. The pyramided lines showed higher BB resistance and submergence tolerance than the recipient parent, Swarna. Culm strength of the pyramided lines showed higher breaking force than the recipient parent, Swarna. The pyramided line, SSBY-16-68-69 yielded the highest grain yield of 7.52 t/ha followed by the lines SSBY-16-68-511 (7.34 t/ha) and SSBY-16-68-1633 (7.02 t/ha). The best-pyramided line showed a yield advantage of 18 % over the recipient parent and 6.8 % over the yield component donor parent. Seven pyramided lines showed higher yield than the recipient parent while 5 lines were better yielder than the yield component donor parent. The pyramided line SSBY-16-68-69 produced 365 grains/panicle while the recipient had 152. The main morphologic and grain quality features of the recipient parent were retained in the pyramided lines.